Meningkatkan Kreativitas Anak Usia Dini melalui Aktivitas Menggambar pada Anak Kelompok A di TK Tunas Karya Indragiri Hulu - Fitria Mareta Sari; Devi Arisandi; Solikah Solikah (Jurnal Pendidikan Tuntas, 2023)
Children's creativity provides the possibility that every child can improve his/her own development in the form of potential and personal qualities. With the natural creative potential that children have, they will foster creative ideas, curiosity and the desire to learn something new. The type of research is Classroom Action Research. The aim of this research is to increase creativity in early childhood through drawing activities for group A children at Tunas Karya Indragiri Hulu Kindergarten. The research results from the highest data are as follows: 72% of children were in the developing according to expectations category in the second cycle compared to only 22% in the first cycle. Furthermore, 17% of children obtained creativity scores in the Very Well Developed category in the second cycle, the previous tie obtained 11% from the first cycle. Finally, 11% of children were still in the Starting to Develop category in the second cycle, from previously obtaining an average score of 39% in the first cycle. Meanwhile, for the Undeveloped category in the first cycle it was 28% to 0% in the second cycle. The increase in the average creativity of group A children at Tunas Karya Indragiri Hulu Kindergarten has met the success indicators so that it does not require reflective action and the research is considered complete. Keywords: Activities, Creativity, Drawing